EVALUATION OF SEGMENTAL RETINAL ARTERITIS WITH OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue Volume 15:Issues 6(2021) (November 2021) - Tsui, Edmund; Leong, Belinda C. S.; Mehta, Nitish; Gupta, Akash; Goduni, Lediana; Cunningham, Emmett T.; Freund, K. Bailey; Lee, Gregory D.; Dedania, Vaidehi S.; Yannuzzi, Lawrence A.; Modi, Yasha S.
Abstract : Purpose: To describe the vascular anatomy and intraluminal flow characteristics of segmental retinal arteritis (SRA) using structural and angiographic optical coherence tomography (OCT). Methods: Retrospective case series of consecutive patients presenting with SRA. All patients were evaluated at presentation with fundus photography, spectral domain OCT, and OCT angiography. One patient was imaged with dense B-scan OCT angiography. Results: Three eyes of three male patients were evaluated. All examinations were consistent with reactivation of ocular toxoplasmosis with an area of active retinochoroiditis adjacent to a focal chorioretinal scar. Spectral domain OCT through areas of SRA noted on clinical examination demonstrated areas of hyperreflectivity circumscribing the affected vessel with a normoreflective lumen. Optical coherence tomography angiography and dense B-scan OCT angiography demonstrated narrowing of the intraluminal flow signal that correlated with areas of segmental hyperreflectivity on spectral domain OCT. Vascular sections proximal and distal to areas of SRA showed normal flow signal. Conclusion: Vessels with SRA demonstrated hyperreflectivity highlighting the vessel wall on spectral domain OCT. Optical coherence tomography angiography showed narrowing of the flow signal within these segments suggesting reduced lumen diameter. Coupling these finding with previous indocyanine green imaging findings in SRA, the collective data suggest the plaques are localized within the vessel wall to either the endothelium or the muscular tunica media without occlusion of the vessel lumen. Abstract : Segmental retinal arteritis results from severe intraocular inflammation and is believed to represent immune deposits within vessel walls. This study further characterizes the structural and angiographic findings of segmental retinal arteritis using optical coherence tomography angiography, localizing the plaque to the vessel wall with corresponding narrowing of the intraluminal area.